Drones delivering automated external defibrillators: A new strategy to improve the prognosis of out-of-hospital cardiac arrest. (January 2023) - Liu, Xiangguo; Yuan, Qiuhuan; Wang, Guoying; Bian, Yuan; Xu, Feng; Chen, Yuguo
Abstract: Background: Out-of-hospital cardiac arrest (OHCA) is a serious threat to human life and health, characterized by high morbidity and mortality. However, given the limitations of the current emergency medical system (EMS), it is difficult to immediately treat patients who experience OHCA. It is well known that rapid defibrillation after cardiac arrest is essential for improving the survival rate of OHCA, yet automated external defibrillators (AED) are difficult to obtain in a timely manner. Objective: This review illustrates the feasibility and advantages of AED delivery by drones by surveying current studies on drones, explains that drones are a new strategy in OHCA, and finally proposes novel strategies to address existing problems with drone systems. Results: The continuous development of drone technology has been beneficial for patients who experience OHCA, as drones have demonstrated powerful capabilities to provide rapid delivery of AED. Drones have great advantages over traditional EMS, and the delivery of AED by drones for patients with OHCA is a new strategy. However, the application of this new strategy in real life still has many challenges. Conclusion: Drones are promising and innovative tools. Many studies have demonstrated that AED delivery by drones is feasible and cost-effective; however, as a new strategy to improve the survival rate of OHCA patients, there remain problems to be solved. In the future, more in-depth investigations need to be conducted.